2008
DOI: 10.1530/eje-08-0306
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of cabergoline as primary and adjunctive treatment for acromegaly

Abstract: Background: Cabergoline is a dopamine agonist that may be used as primary or adjunctive therapy for acromegaly. Although one study suggested biochemical control may be achieved in a substantial proportion of patients, it is still commonly perceived to be a relatively ineffective treatment. Design and method: A prospective audit was performed of 15 consecutive acromegalic patients (eight males, seven females, median age 55, range 31-92 at presentation) treated with cabergoline to determine the effective dose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 24 publications
0
23
1
1
Order By: Relevance
“…The use of CAB as a monotherapy after unsuccessful surgery has only been evaluated in small series, many with pre-selection of patients and with short follow-up periods [3][4][5][15][16][17]. In a recent meta-analysis, the efficacy of CAB as a monotherapy was evaluated, and only 10 studies including a total of 160 patients were found in the literature [15].…”
Section: Cab As An Adjuvant Therapymentioning
confidence: 99%
“…The use of CAB as a monotherapy after unsuccessful surgery has only been evaluated in small series, many with pre-selection of patients and with short follow-up periods [3][4][5][15][16][17]. In a recent meta-analysis, the efficacy of CAB as a monotherapy was evaluated, and only 10 studies including a total of 160 patients were found in the literature [15].…”
Section: Cab As An Adjuvant Therapymentioning
confidence: 99%
“…Higher response rates with normalization of IGF-1 in 20%-33% of patients have been reported in more recent studies using cabergoline. [76][77][78] In prior studies, pretreatment prolactin levels appeared to correlate with IGF-1 response rate to dopamine agonist therapy; however, this effect was not seen in the metaanalysis. Higher baseline prolactin levels did correlate with tumor shrinkage, which occurred in approximately one-third of patients.…”
Section: Dopamine Agonistsmentioning
confidence: 80%
“…Some studies have suggested that co-secretion of prolactin may predict response, but this has not been supported by other studies. 32,33 When used in higher doses (e.g., greater than 3 mg daily) in patients with…”
Section: Dopamine Agonistsmentioning
confidence: 99%